A complete guide to television, field, and digital producing - Cruikshank, Sally Ann; Eschenfelder, Christine C.; Coleman, Keonte (Routledge, an imprint of the Taylor & Francis Group, 2022)
"This book provides an extensive overview of producing in the ever-changing field of journalism for all types of newsrooms. Featuring interviews with renowned journalism professionals, A Complete Guide to Television, Field, and Digital Producing offers an in-depth look at broadcast, field, and digital producing practices of newsrooms today. The book is divided into three sections: television news producing, field producing, and digital producing. Each section provides a clear explanation of the producing role before going into more detail on important skills such as developing stories, writing copy, creating graphics, producing live on location, audience engagement and using social media. Each chapter includes a variety of supplemental material, including discussion questions, keyword definitions, classroom activities, and graded assignments, including rubrics. Written with a combined 64 years of journalism and journalism education experience, the book will prepare students to produce whatever their job requires. Taking an integrated approach to journalism education, this is a vital text for journalism and media students studying digital media, broadcast journalism, social media, and reporting."--Provided by publisher.